The effect of motivation on achieving job satisfaction through organizational justice - A field study on employees of the General Directorates of Education in the Sultanate of Oman – - Alnaimi, Fatma Hamed Mohammed; Sammari, Nouna (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aims at examining the validity of the influence of financial and moral motivation on job satisfaction through organizational justice as a mediator (an influential) variable of personnel at the general directorates of general education in the Sultanate of Oman, as well as investigating the nature of relations within the virtual model of the study, The researcher used a questionnaire as an instrument that was designed based on previous studies of each variable and was distributed to a random sample of (381) individuals from a population of (4137) individuals working in each of the education directorates in sultanate of Oman. The results of the study showed that there is a positive influence of financial and moral motivation on achieving job satisfaction, as the values of the standard evaluations showed that moral incentives will contribute (by 40%) in achieving job satisfaction and that financial incentives will contribute (by 60%) in achieving job satisfaction. The study also concluded that there are significant differences in the moral significance of the influential variable on the relationship between financial and moral motivation and job satisfaction in favor of the samples that support the organizational justice in the concerned public directorates. The study recommends raising the level of job satisfaction of personnel by setting a system for incentives based on justice and objectivity and providing an environment that helps the staff feel positive towards the directorates.